Hearing Loss in Space Flights: A Review of Noise Regulations and Previous Outcomes - Ahmet Uğur Avcı (Journal of International Advanced Otology)
Noise is the primary cause of hearing loss during space flight. Throughout every phase of flight, particularly during launch, a significant amount of noise is generated and transferred via the vehicle’s structure to the places inhabited by the crew. The results of the previous studies provide insights into space flights that may have significant effects on hearing loss. Certain precautions must be taken to ensure the habitability of the spacecraft and prevent potential hearing loss in astronauts or space flight participants.